A Deep Learning Technique To Predict Social Distance And Face Mask (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The impact of covid-19 has changed the lives of many people. Most of the people in the world have lost their employment and their lives too. In order to protect ourselves from this pandemic we need to follow the guidelines given by the World Health Organisation(WHO).The mainly suggested precautions by them are maintaining social distancing and wearing a face mask. We can easily identify whether the persons are following the guidelines given by WHO or not.Here we use Deep Learning Algorithms in order to predict social distancing and face mask detection.